2016
DOI: 10.1111/inm.12198
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' caring and empathy in Jordanian psychiatric hospitals: A national survey

Abstract: Nurses working in psychiatric hospitals need to acquire the skills of therapeutic communication and empathy, and have higher levels of caring. The present study aims to investigate the level of caring and empathy among nurses working in psychiatric hospitals. A cross-sectional survey was utilized to collect data from 205 nurses recruited from three psychiatric hospitals in Jordan. The Background Information Questionnaire, Modified Caring Dimensions Inventory, and Toronto Empathy Questionnaire were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…Most of our results, however, are quite new considering the perspective of the analysis and seem to support previous results that empathy and EI influence the ability to empathise and communicate effectively (Hurley, ; Ioannidou & Konstantikaki, ; Alhadidi et al., ). According to our results and the existing literature, EI is related to communication skills (Shanta & Connolly, ) and empathy (McQueen, ; Stayt, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most of our results, however, are quite new considering the perspective of the analysis and seem to support previous results that empathy and EI influence the ability to empathise and communicate effectively (Hurley, ; Ioannidou & Konstantikaki, ; Alhadidi et al., ). According to our results and the existing literature, EI is related to communication skills (Shanta & Connolly, ) and empathy (McQueen, ; Stayt, ).…”
Section: Discussionsupporting
confidence: 89%
“…In general, according to the literature, empathy and EI strengthen effective communication skills (Alhadidi, Abdalrahim, & Al-Hussami, 2016;Hurley, 2008). Clearly, communication skills, EI and empathy are critical to providing high-quality nursing care and understanding What does this paper contribute to the wider global clinical community?…”
Section: Factors Th At Modulate Communicationmentioning
confidence: 97%
See 1 more Smart Citation
“…- Tanta Scientific Nursing Journal Tanta Scientific Nursing Journal for others in need) and Personal Distress (PD; self-oriented, negative arousal in response to others" distress). (7) The present study revealed that most of the to meet their needs related to hygienic care , feeding and giving medication (20) .…”
Section: Actual Study;mentioning
confidence: 65%
“…Nurses working in psychiatric hospitals need to acquire skills of therapeutic communication and empathy, and have higher levels of caring [19]. The closure of many psychiatric institutions and their substitution with community-based settings, signified that health professionals should perform a variety of new duties, exhibit new skills and develop new perceptions about their work.…”
Section: Introductionmentioning
confidence: 99%